Hodgkin lymphoma – lung metastasis - Case report - Baloski Marjan; Kochovska Kamchevska Nade; Bushev Jane; Smileska Snezana; Buklioska Ilievska, Daniela; Sajkovska Iva; Poposki Bozidar; Trajkovska Vanche (Turkish Respiratory Society; Respiratory Society of Serbia, 2017)
Lymphoma is the most common blood cancer. Occurs when lymphocytes grow and multiply uncontrollably in the lymph nodes, spleen, bone marrow, or other organs. Approximately 9,000 new cases of Hodgkin Lyphoma are projected each year, commonly diagnosed in young adults between the ages of 20 and 34 years. Female patient, 33 years old, diagnosed with Hodgkin Lymphoma in 2010. Treated with several cycles of chemotherapy. 2-3 months before hospital admission, she felt shortness of breath, prolonged, dry cough, haemoptysis. On physical examination – swallen lymph nodes in right axilla and neck. Auscultatory normal finding. Other systems without pathological findings. Chest X-ray - right infraclavicular, massive, heterogenous shadowing, separated and connected to right hylus. CT lung scan – in right upper medial segment, stellate, 6sm, cavernous consolidaton. Mediastinal and hilar lymphaednopathy In right axilla enlarged lymph nodes. Bronchoscopy – edematous mucosa. Abdominal and pelvic CT scan – normal. Transthoracic CT guided lung biopsy with histopathological finding - MORBUS HODGKIN PULMONUM. Microscope finding of fragments showed accumulations of mature lymphocytes mixed with macrophages, plasma cells and eosinophilic leukocytes, rare cells with basophilic cytoplasm and hyperchromatic large cores. In several cells binuclearity, in a larger cell multinuclearity. The immunohistochemical analysis conducted further, obtained the following RESULTS: CD-15 (cell marker for Reed-Sternberg cells) positive +, CD-30 (a marker for cell mitosis in cells) is positive focal +, CD-20 (B-grade. marker) positive +, CD-3 (T marker) positive focal +. For further treatment the patient was referred to the Department of Hematology.
Keywords: Hodgkin's lymphoma; metastasis